Analysis of the quality of life of patients with asthma and allergic rhinitis after immunotherapy - Filanowicz, Małgorzata; Szynkiewicz, Ewa; Cegła, Bernadeta; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Aim : To assess the quality of life of Polish patients with asthma and/or allergic rhinitis before the implementation and after 30–36 months of immunotherapy. Material and methods : Two hundred patients have been involved in the study: 101 with allergic asthma and 99 with pollinosis. In order to collect research material, the Polish versions of AQLQ (Asthma Quality of Life) and RQLQ (Rhinoconjunctivitis Quality of Life) questionnaires have been used. The self-administered questionnaires concerned such data as age, sex and the patients’ subjective evaluation of their quality of life. Results : The average increase in quality of life of patients with asthma was 0.84 and of patients with allergic rhinitis – 1.50. A hypothesis was made that changes of quality of life in each examined group differed significantly. A test for two fractions showed that for patients with asthma it was 7.74 and for patients with allergic rhinitis – 10.38. A statistical analysis showed no such relation in the group of patients with asthma (coefficient of correlation = 0.08) and a slight correlation in the group of patients with allergic rhinitis (coefficient of correlation = 0.20). Applied tests did not show any significant differences, which means that an average increase in quality of life does not depend on sex and age of both examined groups. Conclusions : On the basis of the research conducted among patients before and after a 3-year period of immunotherapy, the following conclusions have been drawn: 1) immunotherapy significantly improves the objective quality of life in both groups; 2) a slight correlation has been identified between the objective and subjective dimension of quality of life amongst patients with asthma, what contributes to a better quality of life; 3) in both study groups, no significant relationship between gender or age and improvement in quality of life has been noted; 4) immunotherapy, from the point of view of the improvement of quality of life, is a valuable therapeutic tool in patients with atopic bronchial asthma and allergic rhinitis.